VIRTUAL TOUR AS AN ALTERNATIVE TO TOURISM DURING COVID-19: A CASE STUDY AT THE ACEH TSUNAMI MUSEUM - Hidayatul Azizi; Iskandar Madjid; Nazli Ismail (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The spread of the coronavirus has had a major impact on the education and tourism sectors, so lockdowns and travel restrictions have prohibited people from traveling. This lockdown policy calls for all activities to be carried out from home, such as work, travel and other outside activities. One of those affected is the Museum, where the Museum as one of the tourist destinations and also education places is affected because it cannot operate. As more and more people stay at home due to the coronavirus pandemic, the need for alternative ways of traveling becomes important. The rapid use of the internet during the pandemic, so that an alternative virtual tour as a substitute for traveling to a place directly becomes a solution. This study aims to evaluate the use of Tsunami Museum virtual tour uploaded in YouTube in 2020 as digital media during the pandemic. This research was conducted using a quantitative-qualitative method with a descriptive approach. Data were obtained from interviews, questionnaires, field observations, photo documentation of activities and literature studies. The results showed that the pandemic made Tsunami Museum manager carry out a digital transformation in educating the public. Virtual Tour uses the zoom application and utilizes social media to promote it. The results of the questionnaire distributed to the virtual tour participants of this museum showed above average of mean standar response from the respondents and were supported by the results of the committee's interview, mentioning that Virtual Tour can help disseminate information on the value of museums related to disaster even during Covid-19.